Prevalence and predictors of fetal macrosomia in southern Vietnam: A cross-sectional study - Ho Thi, Thu Hang; Nguyen Thi, Kim Quyen; Nguyen, Hong Ha; Pham Thi, Ngoc Nga (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Macrosomia, defined as a birth weight of ≥3,500 grams, presents significant health risks for both mothers and newborns. This study aimed to determine the prevalence and associated risk factors of macrosomia among women delivering at 37 weeks or more at Vinh Long General Hospital in the Mekong Delta, Vietnam.Methods: A cross-sectional study was conducted from September 2022 to June 2023, including 1,500 participants. Maternal characteristics and pregnancy-related factors were analyzed to identify associations with macrosomia.Results: The prevalence of macrosomia was 36%, exceeding global averages. Key maternal risk factors included advanced gestational age (≥40 weeks, OR = 1.3, 95% CI: 1.4–2.5, p = 0.02) , parity (OR = 12.4 for single delivery, OR = 3.7 for multiparous women, p < 0.01), and a history of macrosomia (OR = 3.9, p = 0.01). Pre-pregnancy BMI ≥25 kg/m² and excessive gestational weight gain increased the risk by 20.9-fold and 32-fold, respectively.Conclusions: This study highlights the high prevalence of macrosomia in the Mekong Delta and underscores the importance of maternal weight management and prenatal care. Targeted interventions, including nutritional counseling and early risk assessment, are crucial, especially in rural areas with limited healthcare access. The cross-sectional design limits causal inferences, necessitating future longitudinal studies to assess the long-term effects of maternal health interventions and develop effective prevention strategies. Expanding research to other regions in Vietnam and similar low-resource settings can provide a broader perspective on macrosomia prevention and management.